S’sence Sdn Bhd / Ahmad Suhairi Zakaria... [et al.] - Zakaria, Ahmad Suhairi; Syed Othman, Syed Isa; Syed Omar, Sharifah Suhaida; Khalid,, Norwaheda (2000)
S’sence Sdn Bhd is the combination of four young potential entrepreneurs of UiTM Arau Campus, Perlis graduates. The background of this essential oil production is based on the fragrance industry. This is due to the main purpose of this business is to extract the fragrance of lime. This oil that they will product is to give a different smell of the common product that is in the market. For instance, in the cosmetic production, medical (aromatherapy), soap food industry, air freshener and perfume industry. They supply essential oil to that particular industry. This business located at Gurun, Kedah.